Postoperative anion gap associates with short- and long-term mortality after cardiac surgery: A large-scale cohort study - Li, Jiajing; Tian, Yu; Wang, Lingzhi; Chen, Jiayue; Chen, Xiaoshu; Huang, Huansen; Li, Yihao (Frontiers in Cardiovascular Medicine, 2022)
Objective: To investigate whether postoperative anion gap (AG) is associated with short- and long-term mortality in patients following cardiac surgery. Methods: We conducted a retrospective cohort study of adults who underwent cardiac surgery from the Medical Information Mart for Intensive Care - III database. The generalized additive model (GAM), logistic regression, and Cox regression were performed to assess the correlations between AG levels and in-hospital, 90-day, and 4-year mortality. Linear regression was used to evaluate the associations between AG and length of stay (LOS). Results: Totally, 6,410 subjects were enrolled in this study and classified into tertiles based on the initial AG levels. The GAM indicated a positive association between initial AG and in-hospital mortality after adjusting for potential confounders. Multivariate logistic analysis revealed that the risk of in-hospital mortality was higher among patients in tertile 2 (OR 2.05, 95%CI 1.11 3.76, P=0.021) and tertile 3 (OR 4.51, 95%CI 2.57 7.91, P<0.001) compared with those in tertile 1. For 90-day and 4-year mortality, multivariate Cox regression found similar associations between AG tertiles and mortality. The LOS in ICU and hospital also increased as AG tertiles increased. The E-value indicated robustness to unmeasured confounders. Conclusion: This study found a positive association between postoperative AG levels and short- and long-term mortality among patients after cardiac surgery. This relationship warrants further research.